Strengthening Digital Literacy in ELT through the Sutori Platform among Second-Semester English Education Students - Diana Zebua, Sovi Septia; Waruwu, Friska Putri; Gulo , Ferna Ceriah; Telaumbanua, Yasminar Amaerita (Jurnal Pengabdian kepada Masyarakat Nusantara, 2025)
Training on the use of the Sutori digital platform was conducted to improve the ability of prospective English teacher students to create interactive learning media. The training consisted of an introduction to theory and task-based practical exercises. Based on observations, field notes, and questionnaires administered to 10 students, the majority of participants were not familiar with Sutori beforehand but were able to operate its features after the training. Eighty percent of participants felt confident in creating digital instructional materials and intended to use them in microteaching. The practice-based training method proved effective in improving the digital literacy of prospective teachers. Major challenges included varying learning speeds and the need for ongoing guidance. Such digital training is relevant in preparing prospective teachers who are adaptable to technology.